Tinnitus: pathology of synaptic plasticity at the cellular and system levels - Guitton, Matthieu J. (Frontiers in Systems Neuroscience, 2012)
Despite being more and more common, and having a high impact on the quality of life of sufferers, tinnitus does not yet have a cure. This has been mostly the result of limited knowledge of the biological mechanisms underlying this adverse pathology. However, the last decade has witnessed tremendous progress in our understanding on the pathophysiology of tinnitus. Animal models have demonstrated that tinnitus is a pathology of neural plasticity, and has two main components: a molecular, peripheral component related to the initiation phase of tinnitus; and a system-level, central component related to the long-term maintenance of tinnitus. Using the most recent experimental data and the molecular/system dichotomy as a framework, we describe here the biological basis of tinnitus. We then discuss these mechanisms from an evolutionary perspective, highlighting similarities with memory. Finally, we consider how these discoveries can translate into therapies, and we suggest operative strategies to design new and effective combined therapeutic solutions using both pharmacological (local and systemic) and behavioral tools (e.g., using tele-medicine and virtual reality settings).